INTEGRATION BETWEEN THE POPULATION OF JUAZEIRO DO NORTE AND THE ENVIRONMENTAL AREA - ECOLOGICAL PARK OF TIMBAUBAS (Fiep Bulletin - online, 2012)
Building interdisciplinary disciplines – Health Education, Environmental Health and Collective Health – it wasintegrated the theme of the research that led to the design of this work, outlined over two years in FJN - University of Juazeiro,located in Cariri of Ceara- CE. Believing in the great potential that an ecological park can offer to its community as healthyattractive, observing concepts that failed to combine with the impressions reported, we decided to initiate a study which aims atanalyzing the perception of local people of environmental issues in Ecological Park of Timbaubas, checking, specifically, therelation between the population and the environment, in order to develop intervention and integration activities of the localpopulation and the environment. This paper, using a qualitative approach, will be an exploratory and descriptive study, providingcloser ties with the issue, making it, thus, more explicit, improving ideas and raising the opinions, attitudes and beliefs of a certainpopulation, through observation, analysis and register of facts, seeking to understand social relations from both individual andcollective perspectives.
Keywords: social relations; health; environment